Unilateral Inner Mucoperichondrium Flap From Upper Lateral Cartilage and Inferior Mucosal Advancement Flap Technique for Repair of Septal Perforations. Issue 3 (May 2016) - Çomoğlu, Şenol; Şahin, Bayram; Polat, Beldan; Aydemir, Levent; Orhan, Kadir Serkan
Abstract : Background: Many surgical technique have been described for repair of nasal septal perforations with different success rates. This study aimed to describe authors' surgical technique and discuss its results as well as those reported in the literature. Methods: Nineteen patients with nasal septal perforation were operated on between March 2009 and February 2015 at Istanbul University, Istanbul Medical Faculty. The technique described in this article, closure of the perforation with unilateral upper lateral cartilage inner mucoperichondrial flap and inferior meatal advancement flap is an alternative surgical technique. Results: Nineteen patients with symptomatic nasal septal perforation were operated with this technique. All surgical procedures were performed by the same surgeon. Neither intraoperative nor postoperative major complications were observed in any patients. Preoperative and postoperative symptom scores for nasal obstruction, epistaxis, nasal discharge, crusting, whistling, snoring, and olfactory loss as well as overall discomfort levels were compared using a visual analog scale. Complete closure of the perforation was achieved in 18 patients (95%). Conclusions: Small and large perforations may be reliably closed with this technique. Also, this technique can be easily applied via closed or external approach.